Photo-alkali-producing type UV curing adhesive, insulating film and preparation method of photo-alkali-producing type UV curing adhesive
Through the use of photoalkaline-producing UV curing adhesives, the slow curing reaction of modified polyacrylate and epoxy resin is used to solve the problems of low construction efficiency and fast curing rate of battery insulating films, and delayed curing and high efficiency are achieved Curing, suitable for light-transmitting substrates and metal-based substrates, with high shear strength and high temperature resistance.
Patent Information
- Application Number
- CN202411334813.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The construction efficiency of the coating products in the existing battery insulating film is low, the equipment requirements are high, and there are safety hazards. The curing rate of traditional photocuring adhesives is too fast and cannot provide an operable window, and it also provides opaque substrates and metal-based substrates. not applicable.
Develop a photoalkaline-producing UV curing adhesive, including modified polyacrylates, epoxy resins, thiols, photoalkaline-producing agents, photosensitizers and silane coupling agents, catalyzing organic bases for catalyzing thiols by UVA light irradiation The slow curing reaction with epoxy groups forms an interpenetrating network structure to achieve delayed curing and efficient curing.
It provides an operation time of 10-30 minutes, realizes complete curing of the insulating film, and is simple and efficient in construction, avoids the impact of oxygen and metal corrosion problems, and has high shear strength and high temperature resistance.
Smart Images

Figure CN119161831A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesive materials and film materials, and in particular to a photoalkali-generating UV curing adhesive, an insulating film and a preparation method thereof. Background Art
[0002] Generally, there are three application scenarios for battery insulation film products: insulation of end plates and side plates of battery modules, insulation of battery pack boxes, and insulation of other components such as water cooling plates. At present, most of the coating products in battery insulation films are made of structural adhesives such as polyester, polyurethane, epoxy resin, polyolefin, etc., combined with PI film. When in use, it is necessary to laminate by hot pressing, which will lead to low construction efficiency, high requirements for equipment and construction technology, potential safety hazards, and the position cannot be changed after pasting. In comparison, UV curing adhesives have the advantages of simple, fast, efficient and environmentally friendly curing process.
[0003] In order to meet the needs of industrialization, it is necessary to have a certain delayed curing performance, which not only provides a certain operating time for the subsequent process, but also can achieve rapid shaping in a short time. However, the acrylate free radical photopolymerization system traditionally used in the field of photocurable adhesives has a fast curing rate and cannot provide an operational window for overlapping opaque substrates. The use of a photobase-generating UV curing system produces alkaline active species after ultraviolet light irradiation. This process is relatively slow, and then even in dark conditions, it can catalyze the curing reaction, which can achieve the purpose of delay. In addition, there is no oxygen inhibition during the polymerization process and it will not cause corrosion problems to metal substrates. The application prospects are very broad.
[0004] Therefore, it is necessary to develop a photoalkali-generating UV curing adhesive for use in battery insulating films, such as water-cooling plate insulating films. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a photoalkali-generating UV curing adhesive, an insulating film and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a photobase generating type UV curing adhesive is provided, comprising the following raw material components in parts by weight: 100 parts of modified polyacrylate, 25-35 parts of epoxy resin, 15-25 parts of thiol, 4-8 parts of photobase generating agent, 0.1-0.5 parts of photosensitizer, 0.5-1.5 parts of silane coupling agent and 80-120 parts of first organic solvent.
[0007] Preferably, the raw materials for preparing the modified polyacrylate include, by weight: 20-40 parts of soft monomer, 20-40 parts of hard monomer, 5-10 parts of epoxy vinyl monomer, 5-15 parts of heterocyclic functional monomer, 2.5-5 parts of crosslinking monomer, 0.2-0.6 parts of initiator, and 150-250 parts of second organic solvent.
[0008] Preferably, the modified polyacrylate has a solid content of 25%-35%, a weight average molecular weight of 80w-120w, a glass transition temperature of -10°C to 0°C, and contains both carbon-carbon double bonds and epoxy groups in its molecular structure.
[0009] Preferably, the soft monomer is selected from one or more of n-octyl acrylate, isooctyl methacrylate, n-butyl acrylate, lauryl acrylate and octadecyl acrylate;
[0010] The hard monomer is selected from one or more of methyl acrylate, methyl methacrylate and ethyl methacrylate;
[0011] The epoxy-containing vinyl monomer is selected from one or more of glycidyl methacrylate, 3,4-epoxycyclohexylmethyl methacrylate and 3,4-epoxycyclohexyl methacrylate;
[0012] The heterocyclic functional monomer is selected from one or more of dicyclopentadiene acrylate, acryloyl morpholine, isobornyl acrylate, and tetrahydrofuran acrylate;
[0013] The cross-linking monomer is selected from one of acrylic acid, methacrylic acid and β-acryloxypropionic acid.
[0014] The initiator is selected from at least one of an acyl peroxide initiator and an azo compound initiator;
[0015] The second organic solvent is selected from one or more of ethyl acetate, butyl acetate and toluene.
[0016] Preferably, the modified polyacrylate is prepared by the following method:
[0017] S1. In an inert gas atmosphere, the soft monomer, the hard monomer, the epoxy vinyl monomer, part of the heterocyclic functional monomer and part of the second organic solvent are stirred evenly, and the first part of the initiator is first added, and the reaction is carried out at 66.5° C.-67.5° C. for 1 h-2 h to obtain a first reaction solution;
[0018] S2, dropwise adding the remaining heterocyclic functional monomer and the second part of the initiator to the first reaction solution, stirring and reacting at 69° C.-71° C., controlling the dropping time to be 1.5 h-2 h, and continuing the reaction for 0.5-1 h after the dropping is completed, to obtain a second reaction solution;
[0019] S3, adding the remaining third part of the initiator to the second reaction solution, stirring and reacting at 75° C.-78° C. for 3 h-6 h to obtain a third reaction solution;
[0020] S4. Add a cross-linking monomer, a catalyst, and the remaining portion of the second organic solvent to the third reaction solution in sequence, and stir the mixture at 85° C.-90° C. for 3 h-5 h to obtain the modified polyacrylate.
[0021] Preferably, the epoxy resin is composed of bisphenol A epoxy resin and alicyclic epoxy resin in a mass ratio of 1-3:1, wherein the epoxy equivalent of the bisphenol A epoxy resin is 180-240 g / mol, and the epoxy equivalent of the alicyclic epoxy resin is 125-145 g / mol.
[0022] Preferably, the photobase generator is selected from one of WPBG300, WPBG345, TJ-PBG-801, and O0396.
[0023] Preferably, the thiol is selected from one of a trifunctional thiol or a tetrafunctional thiol;
[0024] The photosensitizer is selected from one of ITX, DETX, amine sensitizer EPD, amine sensitizer OPD, TR-PSS-402, and TR-PSS-303;
[0025] The silane coupling agent is selected from one of epoxy-containing silane coupling agents;
[0026] The first organic solvent is selected from one or more of ethyl acetate, butyl acetate and toluene.
[0027] The second aspect of the present invention provides a method for preparing the photobase generating type UV curing adhesive as described above, comprising the following steps: 100 parts of modified polyacrylate, 25-35 parts of epoxy resin, 15-25 parts of thiol, 4-8 parts of photobase generating agent, 0.1-0.5 parts of sensitizer, 0.5-1.5 parts of silane coupling agent and 80-120 parts of first organic solvent are mixed in a mass ratio, and stirred evenly to obtain the photobase generating type UV curing adhesive.
[0028] A third aspect of the present invention provides an insulating film, which is prepared by the following method: uniformly coating the above-mentioned photoalkali-generating UV curing adhesive on an insulating base film, baking at 80-120° C. for 3-8 minutes, and then laminating a release film on the adhesive surface to obtain the insulating film;
[0029] When the insulating film is used, the insulating film is first irradiated with UVA light, and after the release film is torn off, the adhesive surface of the insulating film is attached to the object at room temperature and left to stand until it is completely cured.
[0030] The beneficial effects of the present invention are:
[0031] The present invention provides a photobase-generating UV-curing adhesive, an insulating film and a preparation method thereof. After being irradiated with UVA light (wavelength 365 nm), the photobase-generating UV-curing adhesive provided by the present invention generates an organic base that catalyzes a relatively slow curing reaction of thiol and epoxy group, and has an operable time of 10-30 minutes. After lamination, it only needs to be left standing at room temperature to achieve complete curing. The adhesive has the advantages of delayed curing, simple laminating process, high efficiency and safety.
[0032] The insulating film provided by the present invention adopts anionic photocuring, and the organic nitrogen base generated by the photobase generator is stable in the air, the curing process is not affected by oxygen, and the metal coating is not easily corroded when applied, and the use conditions are very mild. After the adhesive of the present invention is irradiated with light, the remaining carbon-carbon double bonds of the modified polyacrylate are first triggered to undergo Michael addition with thiol, and then the thiol and epoxy group are triggered to undergo ring-opening reaction. The two curing modes act synergistically to form an interpenetrating network structure (IPN), which can reduce the volume shrinkage while maintaining a certain film-forming property.
[0033] In some preferred embodiments, the insulating film of the present invention can achieve the following indicators: at 200°C, 1h, the thermal shrinkage of the insulating film is <0.20%; after the insulating film is attached to an aluminum plate and completely cured, the shear strength is >10MPa and the peel strength is >45N / inch at 23°C; the insulating film of the present invention has the advantages of high shear strength and good high temperature resistance, and has good application prospects in the field of battery insulating films. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the infrared spectrum of the modified polyacrylate prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0036] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0037] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0038] The invention provides a photobase generating type UV curing adhesive, comprising the following raw material components in parts by weight: 100 parts of modified polyacrylate, 25-35 parts of epoxy resin, 15-25 parts of thiol, 4-8 parts of photobase generating agent, 0.1-0.5 parts of photosensitizer, 0.5-1.5 parts of silane coupling agent and 80-120 parts of first organic solvent.
[0039] In a preferred embodiment, the raw materials for preparing the modified polyacrylate include, by weight: 20-40 parts of soft monomers, 20-40 parts of hard monomers, 5-10 parts of epoxy vinyl monomers, 5-15 parts of heterocyclic functional monomers, 2.5-5 parts of cross-linking monomers, 0.2-0.6 parts of initiators, and 150-250 parts of second organic solvents.
[0040] In a preferred embodiment, the modified polyacrylate has a solid content of 25%-35%, a weight average molecular weight of 80w-120w, a glass transition temperature of -10°C to 0°C, and contains both carbon-carbon double bonds and epoxy groups in its molecular structure.
[0041] In a preferred embodiment, the soft monomer is selected from one or more of n-octyl acrylate, isooctyl methacrylate, n-butyl acrylate, lauryl acrylate and octadecyl acrylate.
[0042] In a preferred embodiment, the hard monomer is selected from one or more of methyl acrylate, methyl methacrylate and ethyl methacrylate.
[0043] In a preferred embodiment, the epoxy-containing vinyl monomer is selected from one or more of glycidyl methacrylate, 3,4-epoxycyclohexylmethyl methacrylate and 3,4-epoxycyclohexyl methacrylate.
[0044] In a preferred embodiment, the heterocyclic functional monomer is selected from one or more of dicyclopentadiene acrylate, acryloylmorpholine, isobornyl acrylate, and tetrahydrofuran acrylate.
[0045] In a preferred embodiment, the cross-linking monomer is selected from one of acrylic acid, methacrylic acid, and β-acryloxypropionic acid.
[0046] In a preferred embodiment, the initiator is selected from at least one of an acyl peroxide initiator and an azo compound initiator.
[0047] In a preferred embodiment, the second organic solvent is selected from one or more of ethyl acetate, butyl acetate and toluene.
[0048] In a preferred embodiment, the modified polyacrylate is prepared by the following method:
[0049] S1. In an inert gas atmosphere, the soft monomer, the hard monomer, the epoxy vinyl monomer, part of the heterocyclic functional monomer and part of the second organic solvent are stirred evenly, and the first part of the initiator is first added, and the reaction is carried out at 66.5° C.-67.5° C. for 1 h-2 h to obtain a first reaction solution;
[0050] S2, dropwise adding the remaining heterocyclic functional monomer and the second part of the initiator to the first reaction solution, stirring and reacting at 69° C.-71° C., controlling the dropping time to be 1.5 h-2 h, and continuing the reaction for 0.5-1 h after the dropping is completed, to obtain a second reaction solution;
[0051] S3, adding the remaining third part of the initiator to the second reaction solution, stirring and reacting at 75° C.-78° C. for 3 h-6 h to obtain a third reaction solution;
[0052] S4. Add a cross-linking monomer, a catalyst, and the remaining portion of the second organic solvent to the third reaction solution in sequence, and stir the mixture at 85° C.-90° C. for 3 h-5 h to obtain the modified polyacrylate.
[0053] In a preferred embodiment, the epoxy resin is composed of bisphenol A epoxy resin and alicyclic epoxy resin in a mass ratio of 1-3:1, wherein the epoxy equivalent of the bisphenol A epoxy resin is 180-240 g / mol, and the epoxy equivalent of the alicyclic epoxy resin is 125-145 g / mol.
[0054] In a preferred embodiment, the photobase generator is selected from one of WPBG300, WPBG345, TJ-PBG-801, and O0396.
[0055] In a preferred embodiment, the thiol is selected from a trifunctional thiol or a tetrafunctional thiol.
[0056] In a preferred embodiment, the photosensitizer is selected from one of ITX, DETX, amine sensitizer EPD, amine sensitizer OPD, TR-PSS-402, and TR-PSS-303.
[0057] In a preferred embodiment, the silane coupling agent is selected from one of epoxy-containing silane coupling agents.
[0058] In a preferred embodiment, the first organic solvent is selected from one or more of ethyl acetate, butyl acetate and toluene.
[0059] The present invention also provides a method for preparing the photobase generating type UV curing adhesive as described above, comprising the following steps: mixing 100 parts of modified polyacrylate, 25-35 parts of epoxy resin, 15-25 parts of thiol, 4-8 parts of photobase generating agent, 0.1-0.5 parts of sensitizer, 0.5-1.5 parts of silane coupling agent and 80-120 parts of first organic solvent in proportion by mass, and stirring evenly to obtain the photobase generating type UV curing adhesive.
[0060] The present invention also provides an insulating film, which is prepared by the following method: uniformly coating the above-mentioned photoalkali-generating UV curing adhesive on an insulating base film, baking at 80-120° C. for 3-8 minutes, and then laminating a release film on the adhesive surface to obtain the insulating film;
[0061] When the insulating film is used, the insulating film is first irradiated with UVA light, and after the release film is torn off, the adhesive surface of the insulating film is attached to the object at room temperature and left to stand until it is completely cured.
[0062] After the photobase-generating UV-curing adhesive of the present invention is irradiated with UVA light (wavelength 365nm), the photobase generator and the photosensitizer will gradually decompose to produce an organic nitrogen base. At room temperature, the modified polyacrylate can quickly undergo a Michael addition reaction with the thiol to form a preliminary cure, and can be directly attached to the surface of the adherend at room temperature. Then the organic base continues to induce the thiol to undergo a nucleophilic addition reaction with the epoxy group and epoxy resin on the modified polyacrylate. This reaction is relatively slow at room temperature and will delay curing. There is an operating time of 10-30 minutes. After bonding, it only needs to be left to stand at room temperature to achieve complete curing. Taking the photobase generator O0396 as an example, its reaction mechanism is as follows:
[0063]
[0064] Wherein, R, R1, and R2 all refer to alkyl groups with different numbers of carbon atoms.
[0065] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0066] The sources of the main raw materials involved in the following examples and comparative examples are as follows:
[0067] Isooctyl methacrylate, lauryl acrylate, methyl acrylate, dicyclopentadiene acrylate, and acrylic acid were purchased from Shanghai Hechuang Chemical Co., Ltd.;
[0068] Glycidyl methacrylate, 3,4-epoxycyclohexyl methyl methacrylate, 3,4-epoxycyclohexyl methacrylate, 3,4-epoxycyclohexyl carboxylic acid-3',4'-epoxycyclohexyl methyl ester (TTA21) were purchased from Jiangsu Tetra New Materials Technology Co., Ltd.;
[0069] Azobisisobutyronitrile, tetrabutylammonium bromide, and KH560 were purchased from Sinopharm Reagents and were of analytical grade.
[0070] Bisphenol A epoxy resin E-51 and E-44 were purchased from Baichen Insulation Materials Co., Ltd.;
[0071] Isopropylthioxanthone (ITX) was purchased from Double Bond Chemical Co., Ltd.;
[0072] Photobase generator WPBG300 was purchased from Shanghai Jinpan Biotechnology Co., Ltd.
[0073] Trimethylolpropane tris(3-mercaptopropionate) (TMMP), pentaerythritol tetrakis(3-mercaptopropionate) (PETMP), and dipentaerythritol hexa(3-mercaptopropionate) (DPMP) were purchased from TCI;
[0074] Ethyl acetate and toluene were purchased from Shandong Xinge Chemical Co., Ltd. of industrial grade.
[0075] The main parameters of the modified polyacrylates prepared in the following examples and comparative examples are as follows: solid content of 25%-35%, weight average molecular weight of 90w-110w, and glass transition temperature of -8°C to -2°C.
[0076] Example 1
[0077] A photobase generating type UV curing adhesive, the preparation method of which comprises the following steps: in a light-proof environment, in parts by weight, sequentially adding 100 parts of modified polyacrylate, epoxy resin (20 parts of E-51 epoxy resin, 10 parts of TTA21), 20 parts of thiol (PETMP), 6 parts of photobase generating agent (WPBG300), 0.3 parts of photosensitizer (ITX), 1 part of silane coupling agent (KH560) and 100 parts of a first organic solvent, and stirring and mixing them uniformly to obtain the adhesive.
[0078] In this embodiment, the raw materials for preparing the modified polyacrylate include, by weight:
[0079] Soft monomer: 20 parts of isooctyl methacrylate, 10 parts of lauryl acrylate; hard monomer: 30 parts of methyl acrylate; epoxy vinyl monomer: 8 parts of glycidyl methacrylate; heterocyclic functional monomer: 10 parts of dicyclopentadiene acrylate; cross-linking monomer: 4 parts of acrylic acid; initiator: 0.3 parts of azobisisobutyronitrile; catalyst: 1 part of tetrabutylammonium bromide; organic solvent: 40 parts of toluene and 140 parts of ethyl acetate.
[0080] In this embodiment, the preparation method of modified polyacrylate comprises the following steps:
[0081] S1. Under an inert gas atmosphere, the soft monomer, the hard monomer, the epoxy vinyl monomer, 1 / 2 of the mass of the heterocyclic functional monomer and 1 / 2 of the mass of the second organic solvent are stirred evenly, and 1 / 4 of the mass of the initiator is first added, and the mixture is reacted at 67° C. for 1.5 h to obtain a first reaction solution;
[0082] S2, dropwise add the remaining 1 / 2 mass of the heterocyclic functional monomer and 1 / 4 mass of the initiator to the first reaction liquid, stir and react at 70° C., control the dropping time to 1.5 h, and continue the reaction for 1 h after the dropping is completed to obtain a second reaction liquid;
[0083] S3, adding the remaining 1 / 2 mass of the initiator to the second reaction liquid, stirring and reacting at 76° C. for 4 h to obtain a third reaction liquid;
[0084] S4. Add the crosslinking monomer, the catalyst, and the remaining 1 / 2 mass of the second organic solvent to the third reaction solution in sequence, and stir the mixture at 88° C. for 4 hours to obtain a modified polyacrylate.
[0085] Reference Figure 1 , is the infrared spectrum of the modified polyacrylate prepared in Example 1. It can be seen that at 1634 cm -1 The stretching vibration characteristic peak of C=C appears at 3000cm -1 The stretching vibration peak of =CH appears near 910cm -1 The characteristic absorption peak of epoxy group appears nearby, which confirms that the modified polyacrylate molecule contains both epoxy group and carbon-carbon double bond.
[0086] The polyacrylate prepared in this example has a solid content of 30%, a weight average molecular weight of 100w, and a glass transition temperature of -5°C.
[0087] An insulating film is prepared by the following method: the adhesive prepared above is coated on a PI substrate layer with a thickness of 100 μm using a scraper, the dry adhesive thickness is controlled to be 30±1 μm, and baked at 100°C for 5 minutes, and finally a release film with a thickness of 25 μm is attached to the adhesive surface to prepare an insulating film.
[0088] Example 2
[0089] The only difference between this embodiment and embodiment 1 is that the epoxy vinyl monomer in the raw material for preparing the modified polyacrylate is 8 parts of 3,4-epoxycyclohexylmethyl methacrylate.
[0090] The polyacrylate prepared in this example has a solid content of 31%, a weight average molecular weight of 90w, and a glass transition temperature of -2°C.
[0091] Example 3
[0092] The only difference between this embodiment and embodiment 1 is that the epoxy vinyl monomer in the raw material for preparing the modified polyacrylate is 8 parts of 3,4-epoxycyclohexyl methacrylate.
[0093] The modified polyacrylate prepared in this example has a solid content of 33%, a weight average molecular weight of 115w, and a glass transition temperature of -8°C.
[0094] Example 4
[0095] The difference between this embodiment and embodiment 1 is that the raw materials for preparing the photobase-generating UV curing adhesive include: 20 parts of E-44 epoxy resin and 10 parts of TTA21; and 20 parts of TMMP as the thiol.
[0096] Comparative Example 1
[0097] The only difference between this example and Example 1 is that no epoxy vinyl monomer is added to the raw materials for preparing the modified polyacrylate.
[0098] The modified polyacrylate prepared in this comparative example has a solid content of 31%, a weight average molecular weight of 98w, and a glass transition temperature of -6°C.
[0099] Comparative Example 2
[0100] The only difference between this example and Example 1 is that no cross-linking monomer is added to the raw materials for preparing the modified polyacrylate.
[0101] The modified polyacrylate prepared in this comparative example has a solid content of 29%, a weight average molecular weight of 102w, and a glass transition temperature of -8°C.
[0102] Comparative Example 3
[0103] The only difference between this example and Example 1 is that no heterocyclic functional monomer is added to the raw materials for preparing the modified polyacrylate.
[0104] The modified polyacrylate prepared in this comparative example has a solid content of 27%, a weight average molecular weight of 102w, and a glass transition temperature of -7°C.
[0105] Comparative Example 4
[0106] The only difference between this example and Example 1 is that in the preparation of the photobase-generating UV-curing adhesive, the thiol is 20 parts of DPMP.
[0107] Comparative Example 5
[0108] The only difference between this example and Example 1 is that the epoxy resin used in the preparation of the photoalkali-generating UV curing adhesive is 30 parts of E-44 epoxy resin.
[0109] Comparative Example 6
[0110] The only difference between this example and Example 1 is that no photosensitizer ITX is added in the preparation of the photobase-generating UV curing adhesive.
[0111] Performance Testing
[0112] The insulating films prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to performance tests, and the test items and methods were as follows:
[0113] (1) 180° peel force test: After UV irradiation, the insulating film was attached to the test Al plate within 10 minutes. After standing for 24 hours, 72 hours, and 168 hours, the test was performed according to GB / T 2792-1998 standard. The requirement is: >40N / inch;
[0114] (2) High temperature resistance test: After UV irradiation, the insulating film is left at room temperature for 72 hours, and the length and width dimensions are tested respectively. Then, it is baked at 200°C for 60 minutes. After cooling to room temperature, the length and width dimensions are tested respectively. Then, the dimensional change rate before and after the test is calculated. The requirement is: the maximum dimensional change rate is <0.20%;
[0115] (5) Shear strength test: After UV irradiation, the insulating film is attached to the test Al plate within 10 minutes. After 72 hours, it is tested according to GB / T7124-2008 standard. The requirement is: >10MPa;
[0116] (6) Insulation performance test: 500VDC, 60s, measured according to GB / T 24343-2009 standard, requirement: insulation resistance > 1GΩ;
[0117] (7) High voltage strength test: No breakdown under 1500VDC@60s, requirement: leakage current <0.2mA.
[0118] The test results are shown in Table 1 below:
[0119] Table 1
[0120]
[0121] It can be seen from the test results in Table 1 that in Examples 1-4, after UV irradiation, as the standing time increases, the 180° peel force also increases; when the standing time exceeds 72 hours, the peel force remains almost unchanged, indicating that after 72 hours, the UV curing adhesive of the present invention is basically completely cured; after complete curing, the 180° peel force is all >45N / inch, the shear strength is all >10MPa, and the thermal shrinkage rate is all <0.20%, indicating that the insulating film prepared by the present invention has the advantages of relatively controllable curing time, high shear strength, and good high temperature resistance.
[0122] Compared with the above embodiment:
[0123] Comparative Example 1 does not add epoxy vinyl monomers, and Comparative Example 2 does not add cross-linking monomers. The resulting modified polyacrylates cannot contain C=C and epoxy groups at the same time, and cannot form an IPN structure with the epoxy resin when cured, resulting in low peel force and shear strength of the insulating film after curing, and unqualified performance.
[0124] Comparative Example 3 did not add heterocyclic functional monomers, resulting in poor rigidity of the polyacrylate molecular chain and low cohesive strength, resulting in a peel force of <40N / inch and a shear strength of <9MPa after curing, which was unqualified.
[0125] The thiol added in Comparative Example 4 is DPMP, which contains 6 -SH groups per molecule, resulting in a faster curing rate and a more difficult to control reaction speed. The adhesive layer after curing is hard and brittle, with a peel force of <37 N / inch and a shear strength of <9.5 MPa, which is unqualified.
[0126] Comparative Example 5 did not add alicyclic epoxy resin, which also resulted in a faster curing rate, a hard and brittle adhesive layer, a peel force of <41 N / inch, and a shear strength of <9.5 MPa, which was unqualified.
[0127] In Comparative Example 6, no photosensitizer was added, resulting in a too slow curing rate. After exposure to light and standing for 7 days, the film was not completely cured, and the test performance was unqualified.
[0128] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A photobase-generating UV curing adhesive, characterized in that: The invention comprises the following raw material components in parts by weight: 100 parts of modified polyacrylate, 25-35 parts of epoxy resin, 15-25 parts of thiol, 4-8 parts of photobase generator, 0.1-0.5 parts of photosensitizer, 0.5-1.5 parts of silane coupling agent and 80-120 parts of first organic solvent.
2. The photobase-generating UV curing adhesive according to claim 1, characterized in that: The raw materials for preparing the modified polyacrylate include, by weight: 20-40 parts of soft monomer, 20-40 parts of hard monomer, 5-10 parts of epoxy vinyl monomer, 5-15 parts of heterocyclic functional monomer, 2.5-5 parts of crosslinking monomer, 0.2-0.6 parts of initiator and 150-250 parts of second organic solvent.
3. The photobase-generating UV curing adhesive according to claim 2, characterized in that: The modified polyacrylate has a solid content of 25%-35%, a weight average molecular weight of 80w-120w, a glass transition temperature of -10°C to 0°C, and contains both carbon-carbon double bonds and epoxy groups in its molecular structure.
4. The photobase-generating UV curing adhesive according to claim 2, characterized in that: The soft monomer is selected from one or more of n-octyl acrylate, isooctyl methacrylate, n-butyl acrylate, lauryl acrylate and octadecyl acrylate; The hard monomer is selected from one or more of methyl acrylate, methyl methacrylate and ethyl methacrylate; The epoxy-containing vinyl monomer is selected from one or more of glycidyl methacrylate, 3,4-epoxycyclohexylmethyl methacrylate and 3,4-epoxycyclohexyl methacrylate; The heterocyclic functional monomer is selected from one or more of dicyclopentadiene acrylate, acryloyl morpholine, isobornyl acrylate, and tetrahydrofuran acrylate; The cross-linking monomer is selected from one of acrylic acid, methacrylic acid, and β-acryloxypropionic acid; The initiator is selected from at least one of an acyl peroxide initiator and an azo compound initiator; The second organic solvent is selected from one or more of ethyl acetate, butyl acetate and toluene.
5. The photobase-generating UV curing adhesive according to claim 2, characterized in that: The modified polyacrylate is prepared by the following method: S1. In an inert gas atmosphere, the soft monomer, the hard monomer, the epoxy vinyl monomer, part of the heterocyclic functional monomer and part of the second organic solvent are stirred evenly, and the first part of the initiator is first added, and the reaction is carried out at 66.5° C.-67.5° C. for 1 h-2 h to obtain a first reaction solution; S2, dropwise adding the remaining heterocyclic functional monomer and the second part of the initiator to the first reaction solution, stirring and reacting at 69° C.-71° C., controlling the dropping time to be 1.5 h-2 h, and continuing the reaction for 0.5-1 h after the dropping is completed, to obtain a second reaction solution; S3, adding the remaining third part of the initiator to the second reaction solution, stirring and reacting at 75° C.-78° C. for 3 h-6 h to obtain a third reaction solution; S4. Add a cross-linking monomer, a catalyst, and the remaining portion of the second organic solvent to the third reaction solution in sequence, and stir the mixture at 85° C.-90° C. for 3 h-5 h to obtain the modified polyacrylate.
6. The photobase-generating UV curing adhesive according to claim 1, characterized in that: The epoxy resin is composed of bisphenol A epoxy resin and alicyclic epoxy resin in a mass ratio of 1-3:1, wherein the epoxy equivalent of the bisphenol A epoxy resin is 180-240 g / mol, and the epoxy equivalent of the alicyclic epoxy resin is 125-145 g / mol.
7. The photobase-generating UV curing adhesive according to claim 1, characterized in that: The photobase generator is selected from one of WPBG300, WPBG345, TJ-PBG-801 and O0396.
8. The photobase-generating UV curing adhesive according to claim 1, characterized in that: The thiol is selected from one of a trifunctional thiol or a tetrafunctional thiol; The photosensitizer is selected from one of ITX, DETX, amine sensitizer EPD, amine sensitizer OPD, TR-PSS-402, and TR-PSS-303; The silane coupling agent is selected from one of epoxy-containing silane coupling agents; The first organic solvent is selected from one or more of ethyl acetate, butyl acetate and toluene.
9. A method for preparing a photobase-generating UV curing adhesive as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing 100 parts of modified polyacrylate, 25-35 parts of epoxy resin, 15-25 parts of thiol, 4-8 parts of photobase generator, 0.1-0.5 parts of sensitizer, 0.5-1.5 parts of silane coupling agent and 80-120 parts of first organic solvent according to mass ratio, and stirring evenly to obtain the photobase generating type UV curing adhesive.
10. An insulating film, characterized in that: The insulating film is prepared by the following method: uniformly coating the photobase-generating UV curing adhesive as described in any one of claims 1 to 8 on an insulating base film, baking at 80-120° C. for 3-8 minutes, and then laminating a release film on the adhesive surface to obtain the insulating film; When the insulating film is used, the insulating film is first irradiated with UVA light, and after the release film is torn off, the adhesive surface of the insulating film is attached to the object at room temperature and left to stand until it is completely cured.
Citation Information
Patent Citations
UV-curable composition and adhesive film comprising same, adhesive tape, and adhesive member
CN110643286A
Anionic photocuring thiol-epoxy adhesive
CN113004845A
Pressure-sensitive adhesive as well as preparation method and application thereof
CN117777901A
Deep curable UV adhesives and articles thereof
CN118440629A
Photocuring resin composition and method of manufacturing base material pattern-formed using the same, and electronic component including the base material
JP2013181991A
Cited By
Flavonol derivative photobase generator as well as preparation method and application thereof
CN120365275A
A flavonol derivative photobase generator and its preparation method and application
CN120365275B
